Brain Respiration to Overcome Stress in Working From Home (WFH) Mothers - Efnie Indrianie (Humanitas (Jurnal Psikologi), 2023)
This study aims to determine the effect of Brain Respiration on reducing stress in mothers working from home (WFH). Brain Respiration is a powerful technique to energize the brain because it can regulate emotions that can reduce stress. Fifteen people joined the experimental group and the rest control group. Mothers who were members of the experimental group got Brain Respiration while the control group did not. A biofeedback device measured the degree of stress through electrodermal activity (EDA). The results obtained show that there are differences in the degree of stress in the form of a decrease in the degree of stress in WFH mothers who are included in the experimental group after being given Brain Respiration (T-count = 12, and T-table = 25. If T-count < T-table then H0 rejected). There are also differences in the degree of stress in WFH mothers included in the experimental group and the control group (the results of U-count = 31.5 and U-table = 72). The conclusion can be drawn is that Brain Respiration can reduce stress in WFH mothers.